SHEIKH YAHAYA AGODI'S ROLE IN SHAPING ISLAMIC EDUCATION IN ILORIN EMIRATE, 1931-1995 (LAPAI JOURNAL OF NIGERIA HISTORY, 2024)
This paper examines the enduring influence of Sheikh Yahaya Agodi on the development of Islamic education in the Ilorin Emirate. A prominent scholar and educator until his passing in 1995, Sheikh Agodi was instrumental in advocating educational reforms that integrated traditional Islamic teachings with contemporary knowledge systems. His establishment of educational institutions transformed Ilorin’s educational landscape and nurtured future generations of scholars. This study highlighted Sheikh Agodi's educational philosophy, community engagement, and his initiatives on local and broader Islamic educational practices. Through a qualitative analysis of historical records and contemporary evaluations, the paper underscored Sheikh Agodi’s significant contributions to Islamic education and his legacy in promoting a comprehensive understanding of Islam. Ultimately, this research affirms that Sheikh Yahaya Agodi’s vision continues to inspire discussions about the role of Islamic education in moral and intellectual development within society.